Deforestation, Production Intensity and Land Use under Insecure Property Rights - Gregory S. Amacher; Erkki Koskela; Markku Ollikainen (Center for Economic Studies and ifo Institute (CESifo), 2004)
We propose a framework with endogenous allocation of land between agricultural production, sustainable forest management, and unsustainable forest exploitation in the form of illegal logging to explore deforestation and agricultural and timber supplies when property rights are insecure. Uncertainty over property rights arises through risk of confiscation on sustainably-managed forest land, and through illegal logging activities on frontier native forest land. Confiscation risk is shown to increase deforestation by increasing both land conversion to agriculture and illegal logging. Contrary to current wisdom, we find that higher timber prices do not necessarily lead to an increase in the land used for sustainable forestry, because higher prices stimulate illegal logging activity. Increased monitoring and stronger enforcement reduce illegal logging, and thus deforestation. Confiscation risk decreases timber supply from unsustainable forestry practices while the affect of timber price on timber supply is ambiguous.
Keywords: K42; Q15; Q23; 330; deforestation; property rights; stochastic rotation